2020
DOI: 10.1007/s13659-020-00290-w
|View full text |Cite
|
Sign up to set email alerts
|

Repression of Polyol Pathway Activity by Hemidesmus indicus var. pubescens R.Br. Linn Root Extract, an Aldose Reductase Inhibitor: An In Silico and Ex Vivo Study

Abstract: Development of diabetic cataract is mainly associated with the accumulation of sorbitol via the polyol pathway through the action of Aldose reductase (AR). Hence, AR inhibitors are considered as potential agents in the management of diabetic cataract. This study explored the AR inhibition potential of Hemidesmus indicus var. pubescens root extract by in silico and ex vivo methods. Molecular docking studies (Auto Dock tool) between β-sitosterol, hemidesminine, hemidesmin-1, hemidesmin-2, and AR showed that β-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Initially, the energy-dependent lens pumps are capable of compensating for this but, eventually, become overloaded. This results in liquefaction and swelling of the lens fibers, leading to their degeneration and opacification [ 41 , 42 ]. This process is of particular relevance in young patients with type 1 diabetes [ 43 , 44 ] due to extensive edema of the cortical lens fibers [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, the energy-dependent lens pumps are capable of compensating for this but, eventually, become overloaded. This results in liquefaction and swelling of the lens fibers, leading to their degeneration and opacification [ 41 , 42 ]. This process is of particular relevance in young patients with type 1 diabetes [ 43 , 44 ] due to extensive edema of the cortical lens fibers [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…They found that 100 and 200 mg ethyl acetate treatment will lead to decrease in malondialdehyde and increase in the inorganic phosphorous content ( Kota et al, 2017 ). Phytomolecules like quercetin ( Lan et al, 2020 ), chlorogenic acid ( Kim et al, 2011 ), and β-sitosterol ( Haroon et al, 2020 ) may be responsible for this anticataract property of Alternanthera sessilis (L.) R.Br. ex DC.…”
Section: Introductionmentioning
confidence: 99%
“…This increased oxidative stress and loss of antioxidants consequentially creates the oxidative environment inside the lens, promoting lipid peroxidation, which likely pushes Chol out of the lens membrane, reducing the lens Chol content, diminishing the amount and size of CBDs, and consequentially allowing for increased α-crystallin lens membrane binding. Moreover, dysregulation of the sorbitol pathway can result in fluid accumulation within the lens that causes liquefication and degeneration of the lens fibers [95,98,99]. Separate from the sorbitol pathway, there has also shown to be increased expression of pro-inflammatory cytokines within the lens of diabetic patients that is believed to possibly cause cellular dysfunction and apoptosis [103,104,137].…”
Section: Discussionmentioning
confidence: 99%